2011
DOI: 10.1038/pj.2011.115
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stirring rate on particle formation in emulsifier-free, organotellurium-mediated living radical emulsion polymerization (emulsion TERP) of styrene

Abstract: Particle formation during the initial stages of emulsifier-free organotellurium-mediated living radical emulsion polymerization (emulsion TERP) of styrene at 601C was investigated at two stirring rates (220 and 1000 r.p.m.), in which the styrene phase floated as a layer on an aqueous phase at 220 r.p.m. or became dispersed as droplets at 1000 r.p.m. A water-soluble TERP agent, poly(methacrylic acid) (PMAA)-methyltellanyl (PMAA 30 -TeMe) and a water-soluble thermal initiator, 4,4¢-azobis(4-cyanovaleric acid), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…To study the effect of the concentration of V-501, C i , on particle properties, SFEPs of styrene were carried out changing C i at the constant concentrations of styrene monomer and AIBN. The reason why V-501 was selected was that the particles were synthesized in the SFEP using watersoluble initiator with carboxyl groups at high pH because of ionized initiator radicals derived from the initiators (Gu S. et al, 2004;Moribe H. et al, 2011;Yamada Y. et al, 2005). It was confirmed that the particles were not able to be formed independently by V-501 in normal water.…”
Section: Size Control Using Oil-and Water-soluble Initiators In Sfepmentioning
confidence: 73%
“…To study the effect of the concentration of V-501, C i , on particle properties, SFEPs of styrene were carried out changing C i at the constant concentrations of styrene monomer and AIBN. The reason why V-501 was selected was that the particles were synthesized in the SFEP using watersoluble initiator with carboxyl groups at high pH because of ionized initiator radicals derived from the initiators (Gu S. et al, 2004;Moribe H. et al, 2011;Yamada Y. et al, 2005). It was confirmed that the particles were not able to be formed independently by V-501 in normal water.…”
Section: Size Control Using Oil-and Water-soluble Initiators In Sfepmentioning
confidence: 73%
“…3 wt%) with one order smaller concentration (0.25 mM) of the water-soluble macro-chain transfer agent compared to the emulsion RAFT systems discussed above. [33][34][35][36] Fig. The particle nucleation step is a critically important one in the emulsion polymerization system.…”
Section: Bulk Terp Of Styrenementioning
confidence: 99%
“…[25][26][27] The possible reversible activation processes of TERP are degenerative chain transfer (DT) and thermal dissociation (TD) mechanisms, in which the TD can be negligible below 100°C (Scheme 1). [29][30][31][32][33][34][35][36][37][38] Styrene, acrylates, and methacrylates were used in the emulsion TERP to prepare these polymer particles having a narrow MWD. 28 In our previous work, TERP was successfully applied to an emulsifier-free emulsion polymerization system (emulsion TERP) with poly(methacrylic acid)-methyltellanyl (degree of polymerization of PMAA: 30) (PMAA 30 -TeMe), with the synthesis of well-controlled homopolymers and block copolymers via the DT mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…The consequences of the former and the latter are increase and decrease in particle size, respectively. Regardless of these points, the existence of monomer droplets in SFEP is accompanied by some difficulties such as sensitivity of particle size and particle size distribution on the agitation speed [12, 13], and chemical chain heterogeneity in production of copolymers [14]. Utilizing ethanol as co-solvent, Lio et al [10] restricted the formation of free polyelectrolyte chains and adjusted particle size.…”
Section: Introductionmentioning
confidence: 99%